Índices lipídicos nutricionales y metabólicos en la carne de C. idella alimentados con pellet de Alfalfa (Medicago sativa) - Montenegro, Luciano Federico; Perez, Carolina Daiana; Cunzolo, Sebastián Abel; Descalzo, Adriana Maria (Asociación Argentina de Producción Animal, 2022)
Fish meat provides long-chain n-3 fatty acids: alpha-linolenic acid (ALA; C18:3 n-3), eicosapentaenoic acid (EPA; C20:5 n-3), docosapentaenoic acid (DPA, C22:5 n-3 ) and docosahexaenoic acid (DHA; C22:6 n-3). Knowing the contribution of these in the meat, it is possible to estimate, through nutritional lipid indices, their impact on human health. The most used are the indices of: atherogenicity (AI), thrombogenesis (TI), hypo and hypercholesterolemic (h and H, respectively), peroxidability (PI) and saturation (P/S). The objective of this trial was to study the effect of feeding grass carp (C. idella) juveniles with alfalfa (M. sativa) pellets on nutritional and metabolic lipid indices of meat. Feeding with alfalfa produces an improvement in the FA profile and in the nutritional lipid indices that allow inferring about the action of meat on the health of consumers.